Oleic and stearic acid-coated magnetite nanoparticles for sonication-assisted binary micro-solid phase extraction of endocrine disrupting compounds, and their quantification by GC-MS - Chormey, Dotse Selali; Akkaya, Erhan; Erulas, Fatih Ahmet; Bakirdere, Sezgin (SPRINGER WIEN, 2019)
Nanosized magnetic nanoparticles (MNPs) were utilized for the preconcentration of 12 analytes including pesticides, alkylphenols, hormones and bisphenol A prior to their determination by GC-MS. The extraction efficiency of the MNPs was enhanced by coating them with oleic acid and stearic acid. A binary system consisting of the two kinds of coated MNPs was optimized using a multivariate experimental design which evaluated main experimental variables and their interactions. Under optimized conditions, the following figures of merit are found: (a) Enrichment factors ranging from 64 to 345; (b) detection limits between 0.13 and 2.7 mu g L-1; and (c) recoveries from spiked underground well water and municipal wastewater between 90 and 109%. The closeness of the results to 100% validated the method and underpinned its trueness for quantitative determinations.
Keywords: Pesticides; Endocrine disruptors; Multivariate optimization; Microextraction; BISPHENOL-A; SENSITIVE DETERMINATION; GAS-CHROMATOGRAPHY; TRACE-LEVEL; FATTY-ACIDS; WATER; SAMPLES; ALKYLPHENOLS; Chemistry